If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -3x = 40 Solving 15 + -3x = 40 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -3x = 40 + -15 Combine like terms: 15 + -15 = 0 0 + -3x = 40 + -15 -3x = 40 + -15 Combine like terms: 40 + -15 = 25 -3x = 25 Divide each side by '-3'. x = -8.333333333 Simplifying x = -8.333333333
| 6=m-(3+2m) | | 2(x+6)-5=16 | | -16x^2+66x+13=0 | | 13-3p=-8p-15-7 | | 2x^4-2x-1=0 | | (6x-7)-(8x+5)=0 | | 8x^2-43x-18=0 | | 4(7x+3)-6=28x+6 | | (2t^3-3t^2+5t)-(6t^3+3t^2-5t+8)= | | t=3c-2d | | 4n-19n+12n=18 | | 5/6x-1=-7 | | -4.5y=-11.7 | | 2x+3y=10x+11 | | 3x-16-5x=40 | | y=-0.4x-2.1 | | 6*x=1500 | | 16s-4s-12s+3s=15 | | 0.66x+1=0.50 | | ln(5x+1)=ln(x+11) | | 9x=-11.7 | | 65x-6x=21x+23 | | 6x+6=6(x-5) | | 17h-13h-4h+2h=14 | | 7x-15-10x=15 | | 8x-5=32x-13 | | 11k-9+2k-3= | | 2b+8=2 | | X-8/3=1-x8 | | -1/2•-7=-11 | | -6x-36=-7(1+5x) | | 8b-a-b+a= |